Extraterritorial Implications of Turkish Legislation - Bilgin Tiryakioğlu (Public and Private International Law Bulletin)
Prescriptive jurisdiction of states is based on principles such as territoriality, nationality, passive nationality, universality, and protection. Although jurisdiction to prescribe is limited to the territory of the relevant State, geographic scope of application of any legislation can be determined in an extraterritorial manner. Regardless of the intense discussions on this issue, extraterritorial prescriptive jurisdiction is not considered a violation of international law. Decision of the Permanent Court of International Justice which was rendered in the SS Lotus case was accepted as the basis for objective territoriality principle and effect doctrine. In other words, States can exercise prescriptive jurisdiction for acts and conducts committed abroad that have an impact on their countries. Principle of objective nationality and effect doctrine are not the only basis for the application of legislation of a state to the conducts taking place abroad or persons living in another country. A state can also exercise extraterritorial prescriptive jurisdiction relying on the principle of passive nationality, protection principle or another basis. In Turkish law, geographic scope of application of an act and other legislation are rarely determined expressly on an extraterritorial basis. The extraterritoriality of any rule is defined by interpretation taking into account the purpose of the relevant rule. Extraterritorial application or implication of Turkish law can be seen in various areas such as legislation on anti-trust, personal data protection, anti-corruption, and securities. In addition to legislations regarding these issues, other legislations that have extraterritorial scope of application in Turkish law are discussed in this study.